Users' awareness of and perception on information security issues : a case study of Kulliyyah of ICT postgraduate students - Hamid, Habiba (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2014)
Information security (IS) simply implies the protection and preservation of information; with its central purpose being to protect and preserve the confidentiality, integrity, and availability of information. It may also involve protecting and preserving the authenticity and reliability of information and ensuring that entities can be held accountable. Additionally, putting the educational setting such as International Islamic University Malaysia (IIUM) into consideration, information security awareness (ISA) implies educating the campus community about the inherent risks of the confidentiality, integrity, or availability of systems & data, and how all individuals/students can protect their systems & data. The purpose of this research therefore was to examine users' awareness and perception of IS issues amongst the Kulliyyah of Information and Communication Technology (KICT) post graduate (PG) students of IIUM. To this end, data collection was elicited through the administration of questionnaires and interviews. Data analysis was performed by using the SPSS version 20 on the questionnaire and a qualitative study method that involved breaking the interview into themes was employed for the interview data by determining the commonality among their views. Findings indicated that the participants of this study were conversant with information security issues with a high degree of awareness because most of the participants have up-to-date antivirus to protect them against malware. Furthermore, the majority of the respondents do not entertain emails from unknown sources which also shows how aware they are about IS. However, contrary to some previous studies, no significant statistical difference was observed in the information security awareness level of the male and female participants of this study.